Offering defence against pests and diseases: Bioversity International farmer-researcher field trials mark success at several levels - Bioversity International (2013)
Worldwide, farmers lose more than 25% of their harvests each year due to crop pests and diseases that attack their fields. Pests and diseases not only affect farmers’ family food baskets and income, but they also affect how much food is available on global markets. Ironically, one solution to that loss can be found where the loss is occurring. Consider, for example, that there are some 1,200 varieties of bananas and thousands of varieties of beans – each of these varieties has its own level of resistance to pests, diseases and even to extreme weather conditions that could stem those losses. That is why Bioversity International has set up field trials, working with farmers who plant different varieties of the same crops next to each other in their fields, to see which combinations provide the most effective control against which pests and diseases. Initial results from around the world indicate change. Ugandan farmers have seen the presence of weevils that attack banana plants reduced by 75%. Smallholder farmers in Ecuador who planted diverse bean varieties harvested their crop in spite of a heat wave, while those who invested in one commercial variety lost everything. Chinese farmers in the mountains of Sichuan and Yunnan provinces identified their most resistant traditional maize and rice varieties and established community seedbanks to make them available. The Government of Morocco produced a film promoting the importance of genetic diversity in reducing crop pests and diseases for the general public.